Implementation of schizophrenic eye gaze and head movement onto avatar platform - Ng, Yan Jun (2019)
This project aims to create an avatar which has the capability to interact with human inputs in real time while being able to display the characteristic of a schizophrenic patient. The avatar Nicole was created with blender while the animations for Nicole were animated within Unity and Microsoft Visual Studio.